Apolipoprotein A1 Protects Against Necrotic Core Development in Atherosclerotic Plaques: PDZK1-Dependent High-Density Lipoprotein Suppression of Necroptosis in Macrophages. Issue 1 (10th November 2022) - Kluck, George E.G.; Qian, Alexander S.; Sakarya, Emmanuel H.; Quach, Henry; Deng, Yak D.; Trigatti, Bernardo L.
Abstract : Background: Atherosclerosis is a chronic disease affecting artery wall and a major contributor to cardiovascular diseases. Large necrotic cores increase risk of plaque rupture leading to thrombus formation. Necrotic cores are rich in debris from dead macrophages. Programmed necrosis (necroptosis) contributes to necrotic core formation. HDL (high-density lipoprotein) exerts direct atheroprotective effects on different cells within atherosclerotic plaques. Some of these depend on the SR-B1 (scavenger receptor class B type I) and the adapter protein PDZK1 (postsynaptic density protein/Drosophila disc-large protein/Zonula occludens protein containing 1). However, a role for HDL in protecting against necroptosis and necrotic core formation in atherosclerosis is not completely understood. Methods: Low-density lipoprotein receptor–deficient mice engineered to express different amounts of ApoA1 (apolipoprotein A1), or to lack PDZK1 were fed a high fat diet for 10 weeks. Atherosclerotic plaque areas, necrotic cores, and key necroptosis mediators, RIPK3 (receptor interacting protein kinase 3), and MLKL (mixed lineage kinase domain-like protein) were characterized. Cultured macrophages were treated with HDL to determine its effects, as well as the roles of SR-B1, PDZK1, and the PI3K (phosphoinositide 3-kinase) signaling pathway on necroptotic cell death. Results: Genetic overexpression reduced, and ApoA1 knockout increased necrotic core formation and RIPK3 and MLKL within atherosclerotic plaques. Macrophages were protected against necroptosis by HDL and this protection required SR-B1, PDZK1, and PI3K/Akt pathway. PDZK1 knockout increased atherosclerosis in LDLR KO mice, increasing necrotic cores and phospho-MLKL; both of which were reversed by restoring PDZK1 in BM-derived cells. Conclusions: Our findings demonstrate that HDL in vitro and ApoA1, in vivo, protect against necroptosis in macrophages and necrotic core formation in atherosclerosis, suggesting a pathway that could be a target for the treatment of atherosclerosis.